PENERAPAN BUSINESS SYSTEM PLANNING UNTUK PERENCANAAN PEMBANGUNAN SISTEM INFORMASI AKADEMIK (Studi Kasus : Universitas Siliwangi) - Gea Aristi (LPPM Universitas Bina Sarana Informatika, 2014)
Information system in business organization becomes very important related to the time accuracy and information supply correctness that needed by the user. The first step to build information system is making plan. One of methodologies in making information system plan is the arrangement of strategical plan that is done by using Business System Planning (BSP). This methodology is related to the effort how the information system should be structuralized, integrated, and implemented by organization in long period. Siliwangi University is one of university in Tasikmalaya that has a mission to increase the work of Tri Dharma. One of them is academical function. The academical information system today still has some lacks, like inaccurate, incomplete, and ambiguous data. Besides that there is still a difficult thing in accessing and processing data. So it needs to do the observation about the implementation of Business System Planning for the planning of academical information system building that can help Siliwangi University fulfill the needs and run the business strategy. The step which done by this Business System Planning methodology are business goals definition, business process, data classes, information architecture and integration.